Pemanfaatan Media Kahoot dalam Minat Belajar Siswa Kelas X SMA Al-Jamiatu Daalatul Jannah Sungkai Barat - Widara Rizqi Ulfa; Lisa Amillina; Ahmad Agung Safaat; Dessy Kurnia Mulyani (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This study aims to determine whether interactive learning media based on Kahoot can increase students' interest in learning. Kahoot is a single media application that can be used in online learning that contains quizzes and games. Interactive learning media such as Kahoot can be used in teaching and learning activities such as holding pretests, practicing questions, reinforcing materials, remedial, and others. The purpose of this study is to determine students' understanding by applying Kahoot as an effective learning medium. This study uses a qualitative method design using a location setting, namely Al Jamiatu Dalatul Jannah High School. Data collection techniques in this study are using observation and interviews